How ionic strength affects the conformational behavior of human and rat beta amyloids--a computational study - Kříž, Zdeněk; Klusák, Jiří; Krištofíková, Zdena; Koča, Jaroslav (PloS one, 2013)
Progressive cerebral deposition of amyloid beta occurs in Alzheimers disease and during the aging of certain mammals (human, monkey, dog, bear, cow, cat) but not others (rat, mouse). It is possibly due to different amino acid sequences at positions 5, 10 and 13. To address this issue, we performed series of 100 ns long trajectories (each trajectory was run twice with different initial velocity distribution) on amyloid beta (1-42) with the human and rat amino acid sequence in three different environments: water with only counter ions, water with NaCl at a concentration of 0.15 M as a model of intracellular Na(+) concentration at steady state, and water with NaCl at a concentration of 0.30 M as a model of intracellular Na(+) concentration under stimulated conditions. We analyzed secondary structure stability, internal hydrogen bonds, and residual fluctuation. It was observed that the change in ionic strength affects the stability of internal hydrogen bonds. Increasing the ionic strength increases atomic fluctuation in the hydrophobic core of the human amyloid, and decreases the atomic fluctuation in the case of rat amyloid. The secondary structure analyses show a stable α-helix part between residues 10 and 20. However, C-terminus of investigated amyloids is much more flexible showing no stable secondary structure elements. Increasing ionic strength of the solvent leads to decreasing stability of the secondary structural elements. The difference in conformational behavior of the three amino acids at position 5, 10 and 13 for human and rat amyloids significantly changes the conformational behavior of the whole peptide.
Keywords: vodíková vazba; Humans; povrchové vlastnosti; Protein Stability; Protein Structure, Secondary; Hydrophobic and Hydrophilic Interactions; Molecular Sequence Data; molekulární sekvence - údaje; chlorid sodný; krysa rodu Rattus; lidé; sekundární struktura proteinů; zvířata; amyloidní beta-protein; stabilita proteinů; osmolární koncentrace; simulace molekulární dynamiky; Amino Acid Sequence; Peptide Fragments; Amyloid beta-Peptides; Molecular Dynamics Simulation; voda; Hydrogen Bonding; peptidové fragmenty; Rats; Water; Animals; Sodium Chloride; terciární struktura proteinů; Protein Structure, Tertiary; Osmolar Concentration; Surface Properties; hydrofobní a hydrofilní interakce; sekvence aminokyselin